Numerical Simulation of Ocean Wave Using High-Order Spectral Modeling Techniques: Its Influence on Transport Sediment in Benoa Bay, Bali, Indonesia - Ulung Jantama Wisha; Try Al Tanto; Widodo Pranowo; Semeidi Husrin; Gunardi Kusumah; agus Maryono (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2019)
Benoa Bay is threatened by sedimentation issue within the bay. It impairs the water mass circulation, influencing scour, mixing, and turbulence as well as sediment transport processes. This study focuses on the wave characteristic and its relation to sediment transport within Benoa Bay. Spectral wave modeling techniques were employed. The equation was discretized based on the condition of winds, tidal, and currents. Total sediment transported was calculated according to the wave model result. Total suspended sediment (TSS) model was simulated which the simulation considers bed load and suspended load transport. Significant wave height (Hs) ranged 0-0.48 m and 0-0.44 m during high tidal condition and low tidal condition respectively. Wave undulation propagates toward the West and Northwest within Bay. The wave period (Ts) ranged 2-6.5 second. Total sediment transport ranged 2828.16 - 86235.66 m3/year. TSS concentration ranged 1-100 mg/L and 1-155 mg/L during high tidal condition and low tidal condition respectively. Those conditions indicate that the sedimentation has been extremely occurred within the bay. The areas around Benoa peninsula, Benoa harbor, and Serangan Island are heavily polluted by suspended sediment. Bottom sediment is stirred by hydraulic jump off wave propagation. The first wave crest induces scour, which its train carries the stirred sediment entering the bay. If ongoing, this condition will exacerbate the existing ecosystem. Benoa Bay development has a big role evoking the level of TSS and turbidity. The more the sedimentation occurs, the more the ecological problem takes place.